BMP signaling inhibition in Drosophila secondary cells remodels the seminal proteome and self and rival ejaculate functions - Hopkins, B; Sepil, I; Bonham, S; Miller, T; Charles, P; Fischer, R; Kessler, B; Wilson, C; Wigby, S (National Academy of Sciences, 2019)
Seminal fluid proteins (SFPs) exert potent effects on male and female fitness. Rapidly evolving and molecularly diverse, they derive from multiple male secretory cells and tissues. In Drosophila melanogaster, most SFPs are produced in the accessory glands, which are composed of ∼1,000 fertility-enhancing "main cells" and ∼40 more functionally cryptic "secondary cells." Inhibition of bone morphogenetic protein (BMP) signaling in secondary cells suppresses secretion, leading to a unique uncoupling of normal female postmating responses to the ejaculate: refractoriness stimulation is impaired, but offspring production is not. Secondary-cell secretions might therefore make highly specific contributions to the seminal proteome and ejaculate function; alternatively, they might regulate more global-but hitherto undiscovered-SFP functions and proteome composition. Here, we present data that support the latter model. We show that in addition to previously reported phenotypes, secondary-cell-specific BMP signaling inhibition compromises sperm storage and increases female sperm use efficiency. It also impacts second male sperm, tending to slow entry into storage and delay ejection. First male paternity is enhanced, which suggests a constraint on ejaculate evolution whereby high female refractoriness and sperm competitiveness are mutually exclusive. Using quantitative proteomics, we reveal changes to the seminal proteome that surprisingly encompass alterations to main-cell-derived proteins, indicating important cross-talk between classes of SFP-secreting cells. Our results demonstrate that ejaculate composition and function emerge from the integrated action of multiple secretory cell types, suggesting that modification to the cellular make-up of seminal-fluid-producing tissues is an important factor in ejaculate evolution.